Najnowsza leksyka polska w Wikisłowniku – problemy identyfikacji jednostek - Niekrewicz, Agnieszka A. (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The aim of the article is to present the opportunities that the Polish-language variant of Wiktionary offers for researching new vocabulary and to indicate methods for extracting the latest Polish vocabulary from it. The author discusses examples of new lexicon recorded in Wiktionary (word-formation derivatives, neo-semanticisms, borrowings and phraseological units) and verifies its presence in other sources to determine the usefulness of the social dictionary in lexical research.